2019
DOI: 10.1007/s11240-019-01656-w
|View full text |Cite|
|
Sign up to set email alerts
|

Positive effect of AgNPs and AuNPs in in vitro cultures of Lavandula angustifolia Mill.

Abstract: The aim of this study was determined how an addition of gold nanoparticle (AuNPs) and silver NPs (AgNPs) into culture media affects plant development and formation of oil glands in narrow-leaved lavender (Lavandula angustifolia) cv. 'Munstead'. Plant shoots were propagated on media supplemented with 1, 2, 5, 10, 20 and 50 mg dm −3 AuNPs or AgNPs (diameter of 24.2 ± 2.4 nm and 27.5 ± 4.8 nm). Both of NPs positively influenced the growth and development of lavender propagated in vitro. The culture media with NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Additionally, CuO and ZnO NPs also caused a significant increase in total antioxidant capacity, reducing power and DPPH radical scavenging capacity of the extracts from shoots of the same species [29,52]. There are no studies about the impact of the same type of NPs on the antioxidant activity of plants from the genus Lavandula and Thymus however, it was reported that Ag and Au NPs increased the ABTS free radical scavenging capacity in cultures of L. angustifolia [35].…”
Section: Antioxidant and Enzymes Inhibitory Activities: Correlation With Phenolic Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, CuO and ZnO NPs also caused a significant increase in total antioxidant capacity, reducing power and DPPH radical scavenging capacity of the extracts from shoots of the same species [29,52]. There are no studies about the impact of the same type of NPs on the antioxidant activity of plants from the genus Lavandula and Thymus however, it was reported that Ag and Au NPs increased the ABTS free radical scavenging capacity in cultures of L. angustifolia [35].…”
Section: Antioxidant and Enzymes Inhibitory Activities: Correlation With Phenolic Compositionmentioning
confidence: 99%
“…Moreover, it has been shown that the application of nano-iron oxide increases the absorption and uptake of important macronutrients in several plant species [32][33][34]. On the other hand, the addition of other NPs such as Au and Ag at different concentrations positively affected in vitro growth and development of another Lavandula species, L. angustifolia [35].…”
Section: Biometric and Physiological Featuresmentioning
confidence: 99%
“…This previous method did not apply for all cases of orchid rooting, which needs a special handling. The use of nanomaterials in enhancing the plant rooting and its growth under in vitro conditions has become recently a promising tool such as silver nanoparticles (Thangavelu et al 2018;Saha and Gupta 2018;Jadczak et al 2019;Ha et al 2020;Tymoszuk•and Kulus 2020), iron nanoparticles (Mozafari et al 2018 and Khan et MAYADA K. SELIEM et al al. 2020), zinc oxide nanoparticles (Nalci et al 2019;Abdel Wahab et al 2020; Mazaheri-Tirani and Dayani 2020), cobalt nanoparticles (Ha et al 2020), gold nanoparticle (Jadczak et al 2019), copper oxide nanoparticles (Javed et al 2017 andNalci et al 2019), copper nanoparticles (Ibrahim et al 2019), nickel oxide nanoparticles (Pinto et al 2019), and nano-Se (Sotoodehnia-Korani et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are of biological or non-biological origin and can recognize cytoplasmic membrane receptors on the plant cells. Recognition and binding led to signal elicitation, which stimulates the expression of genes related to secondary metabolite production [20][21][22]. The elicitors work as plant stressors in a natural environment: they can be represented by fungi, bacteria, activated enzymes, and other biological compounds [22,23].…”
Section: Introductionmentioning
confidence: 99%